Rationality in The Pattern of Appointment and Dismissal Of Village Equipment Post Village Head Election in Pesawaran District Lampung Province - Marzuki Marzuki; Mansyur Achmad; Karno Karno (Lembaga Riset dan Inovasi Al-Matani, 2023)
The background of this research is the dismissal and appointment of Village Apparatuses after the election of the village head in Pesawaran District. The dismissal and Appointment of village apparatuses that occurred in Pesawawan District included those who followed the rules and some who were not based on the rules. The